Pengaruh Cryprotectant Agents (Gliserol) pada Media Preservasi Terhadap Daya Simpan Pseudomonas aeruginosa FNCC 0063 - Rasyidah, Rasyidah; Fariani, Rini (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
Preservation using glycerol as cryoprotectant agents is expected to be an alternative in maintaining bacterial viability, so that when they are to be used again, the bacteria can grow. The objective of this study was to determine the effect of glycerol concentrations of 10%, 30%, and 50% in the preservation medium and preservation time on the viability of Pseudomonas aeruginosa FNCC 0063 during storage, as well as to determine the effective glycerol concentration and time. Preservation of Pseudomonas aeruginosa FNCC 0063 in the form of bacterial suspensions and pellets was conducted for 30–150 days at a freezer temperature of –40°C. Viability tests were performed from day 30 to 150 using the Plate Count method with Nutrient Agar medium. Two-way ANOVA test of pellet preservation from cell viability data,  significant value 0.000 < 0.05, meaning that viability or the number of living cells is influenced by time and glycerol concentration. Preservation time and glycerol concentration based on the Tukey test results showed the highest average value on day 60 and a concentration of 50%, which was 9.4 x 10⁵ CFU/ml. Suspension preservation: the two-way ANOVA test results showed that preservation time had an effect, but glycerol concentration did not significantly affect cell viability. Tukey test showed that the preservation results on day 120 were significantly different from those at 30–90 days. As for concentration treatment, there were no significant differences between 10%, 30%, and 50%, but the 50% concentration had relatively stable and high viability compared to 10% and 30%, at 6.7 × 10⁵ CFU/ml.